Nanopore sequencing for rapid diagnostics of salmonid RNA viruses. Issue 1 (December 2018) - Gallagher, Michael; Matejusova, Iveta; Nguyen, Lien; Ruane, Neil; Falk, Knut; Macqueen, Daniel
Abstract Analysis of pathogen genome variation is essential for informing disease management and control measures in farmed animals. For farmed fish, the standard approach is to use PCR and Sanger sequencing to study partial regions of pathogen genomes, with second and third-generation sequencing tools yet to be widely applied. Here we demonstrate rapid and accurate sequencing of two disease-causing viruses affecting global salmonid aquaculture, salmonid alphavirus (SAV) and infectious salmon anaemia virus (ISAV), using third-generation nanopore sequencing on the MinION platform (Oxford Nanopore Technologies). Our approach complements PCR from infected material with MinION sequencing to recover genomic information that matches near perfectly to Sanger-verified references. We use this method to present the first SAV subtype-6 genome, which branches as the sister to all other SAV lineages in a genome-wide phylogenetic reconstruction. MinION sequencing offers an effective strategy for fast, genome-wide analysis of fish viruses, with major potential applications for diagnostics and robust investigations into the origins and spread of disease outbreaks.